Classes of physical geography and methodologies applicable to the school environment - Sousa, Marcos Gomes de; Cordeiro Junior, Iran de Oliveira; Albuquerque, Emanuel Lindemberg Silva (Geosaberes; Vol 10 No 22 (2019): Sept - Dec, 2019)
When considering the importance of the study of the methodologies applied to the contents of Geography, we see the need for a close relationship, in the teaching / learning process, between theory and practice. In this way, the objective is to perform an analysis and reflection of the methodologies applicable to the teaching of Physical Geography, considering the potential of the conceptual maps, mockup and fieldwork, with reference to the experiences acquired in the Program Institutional of Initiation Scholarships the Teacher (Pibid). The methodological procedure was based on bibliographical reviews on the central theme. It is noted that learning methods and tools must be applied in the school environment, given that the resources and methodologies emerge to meet the needs that are present in teaching and learning geographic.